2019
DOI: 10.1016/j.msard.2018.10.116
|View full text |Cite
|
Sign up to set email alerts
|

A first investigation of tongue, lip, and jaw movements in persons with dysarthria due to multiple sclerosis

Abstract: Background: Multiple sclerosis can affect the speech motor system and result in dysarthria. Objectives: This pilot study sought to identify tongue, lip, and jaw motor deficits in persons with dysarthria due to multiple sclerosis (PwDMS) to better understand the speech motor mechanisms that underlie their aberrant speech. Methods: Tongue and jaw movements during /ai/ and lower lip and jaw movements during /bob/ were examined in eleven PwDMS and fourteen age- and sex-matched controls using threedimensional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…These findings provide value when considering functional outcomes for potential surgical candidates, as patients requiring surgical techniques that impede jaw movement may experience worse functional speech outcomes than those who do not. Similar findings have been reported in populations with impaired speech motor control such as multiple sclerosis (55) and amyotrophic lateral sclerosis (56,57) or during normal speech motor development in neurotypical children (58).…”
Section: Individuals In Early and Late Stages Of Neuromotor Recovery supporting
confidence: 87%
“…These findings provide value when considering functional outcomes for potential surgical candidates, as patients requiring surgical techniques that impede jaw movement may experience worse functional speech outcomes than those who do not. Similar findings have been reported in populations with impaired speech motor control such as multiple sclerosis (55) and amyotrophic lateral sclerosis (56,57) or during normal speech motor development in neurotypical children (58).…”
Section: Individuals In Early and Late Stages Of Neuromotor Recovery supporting
confidence: 87%
“…Mefferd et al conducted a pilot study to investigate the tongue, lip, and jaw movements in individuals suffering from dysarthria due to multiple sclerosis. 5 The study concluded that the ability of these individuals to move their tongue with adequate speed was significantly compromised, leading to a slow speech rate in such subjects. Similar to these studies, our present study also observed alterations in tongue mobility in the early and late stages of OSMF.…”
Section: Discussionmentioning
confidence: 99%
“…Not only in healthy individuals, but clinical assessment of the tongue has also been performed in subjects with disorders such as ankyloglossia, skeletal Class II malocclusion, and multiple sclerosis. 3 , 4 , 5 , 10 A study by Jamilian et al examined the relationship between the classification of ankyloglossia and the mobility of the tongue. 3 The tongue mobility was assessed according to Kotlow's criteria, which included touching the upper and lower lips with the tip of the tongue without any strain, retrusion of the tongue without blanching of tissue, and no exhibition of difficulty in speech associated with limited tongue mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mefferd et al 21 estimated with kinematic measurements that speech movements of the tongue are more impaired than lower lip movements in persons with MS. Future studies should make clear which compensatory technique improves speech intelligibility.…”
Section: Current Developments and Future Perspectivesmentioning
confidence: 99%